The Ateneo macroeconomic and forecasting model - Rodriguez, U-Primo E.; Briones, Roehlano M. (2002)
The Ateneo Macroeconomics and Forecasting Model (AMFM) is a small quarterly macroeconometric model of the Philippine economy. Designed for forecasting and policy analysis, the model generates results for key macroeconomic indicators.